2007
DOI: 10.2174/138955707780619653
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Therapy of Cushings Syndrome: Drugs and Indications

Abstract: Agents that inhibit steroidogenesis are useful in all forms of Cushing's syndrome and are effective in about 70% of patients. Main indications for drug therapy include preparation for surgery, persistence or recurrence after surgery, while awaiting for the effect of radiation therapy, occult ectopic ACTH syndrome, severe hypercortisolism and malignancy related hypercortisolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 194 publications
0
31
0
1
Order By: Relevance
“…The patient developed acute exacerbation of IPF shortly after his hypercortisolemia was controlled using oral metyrapone, an adrenal steroidogenesis inhibitor (7,8). Previous studies have suggested a possible role of surgical pulmonary procedures, bronchoscopy, or radiation therapy for lung cancer in the onset of acute exacerbation of IPF (9-12).…”
Section: Discussionmentioning
confidence: 99%
“…The patient developed acute exacerbation of IPF shortly after his hypercortisolemia was controlled using oral metyrapone, an adrenal steroidogenesis inhibitor (7,8). Previous studies have suggested a possible role of surgical pulmonary procedures, bronchoscopy, or radiation therapy for lung cancer in the onset of acute exacerbation of IPF (9-12).…”
Section: Discussionmentioning
confidence: 99%
“…Metyrapone is an orphan medication that holds the FDA approval for the diagnosis of Cushing's syndrome and is occasionally used off-label for short-term treatment of Cushing's syndrome before surgery. However, treatment with metyrapone or other steroidogenic inhibitors is usually discouraged because of poor tolerability and the contradictory increase in ACTH production and mineralocorticoid effects (Díez and Iglesias, 2007;Traina et al, 2013). Therefore, alternative medical treatments for the curtailing of HPA-axis activity are needed.…”
Section: Po0mentioning
confidence: 99%
“…A gyógyszer hatása a vizeletkortizol-ürítéssel nyomon követhető. A betegek mintegy 15%-ában a máj-enzimek szérumszintje jelentősen növekedhet, amelyet betegünknél nem tapasztaltunk [8,10].…”
Section: Megbeszélésunclassified